College STEM Students’ Adjustment, Coping, and Stress during the COVID-19 Pandemic - Ding, Yi; Zhang, Anqi; Hu, Xiaoyan; Wang, Qian (Advances in Social Sciences Research Journal, 2025)
The COVID-19 pandemic profoundly affected higher education, disrupting both the academic and personal lives of students. This study investigates differences in academic adjustment, perceived stress, and coping mechanisms between STEM (Science, Technology, Engineering, Mathematics) and non-STEM students during the pandemic. Secondary analyses were conducted on survey responses from 216 participants (n = 108 STEM students, n = 108 non-STEM students) drawn from a larger study focused on university adaptation, perceived stress, coping strategies, and COVID-19-specific factors. The results revealed that non-STEM students adjusted better academically compared to their STEM counterparts, with a greater tendency to use escape-avoidance coping strategies. However, there were no significant differences between the two groups in social or personal-emotional adjustment, nor in overall stress levels despite the varying academic pressures. Regression analysis identified academic adjustment, emotional adjustment, and avoidance behaviors as key predictors of perceived stress and COVID-19-related challenges. These findings highlight the need for tailored support systems to address the distinct challenges faced by students in different academic disciplines, particularly during crises. The study concludes with a discussion of the implications, limitations, and future research directions.